Evaluation of a digital entomological surveillance planning tool for malaria vector control: Three country mixed methods pilot study - Charlotte Hemingway; Steven Gowelo; Mercy Opiyo; Dulcisaria Marrenjo; Mara Maquina; Blessings N. Kaunda-Khangamwa; Lusungu Kayira; Teklu Cherkose; Yohannes Hailemichael; Neusa Torres; Estevao Mucavele; Muanacha Mintade; et al. (PLoS ONE, 2025)
Background Vector control remains the principal method to prevent malaria transmission and has led to significant reductions in malaria incidence across endemic regions. However, such gains have stagnated, underscoring the need to tailor vector control to local drivers of transmission. An Entomological Surveillance Planning Tool (ESPT) was designed to translate normative guidance into an operational tool that supports cost effective, locally tailored, and evidence-based vector control. To facilitate ESPT implementation, an interactive digital toolkit (eSPT) was created to support question-based surveillance planning. Methods The eSPT was evaluated with 49 target users in Ethiopia, Malawi, and Mozambique. The eSPT was introduced to participants through facilitated workshops. A mixed-methods design was employed, combining pre- and post-intervention surveys with qualitative measures to assess the impact of the eSPT on knowledge, self-efficacy and work practices related to entomological surveillance planning. Qualitative methods were used to explore the acceptability and utility of the eSPT. Results Quantitative measures showed that the facilitated eSPT workshop increased participants’ knowledge and self-efficacy in question-based entomological surveillance planning. Target users responded positively to the eSPT, reporting high usability scores and satisfaction with the interface. Respondents from academic institutes, central government and international NGOs reported the eSPT to be a useful training tool and believed it could provide substantial efficiencies in the planning process. Further user testing, customizability and compatibility with mobile devices was recommended to enhance the eSPT’s usefulness as a planning tool, especially at the local government level. Conclusions Interactive digital toolkits could be an engaging, efficient, and accessible way to build research and surveillance capacity within relevant organizations and local authorities. This is achieved by combining tailored information and guidance, with functions that enable the development of a planning document, in an easy-to-follow stepwise process. To maximize the usability and usefulness of these toolkits, target users must be centered in the design.